Changes in brainstem pain modulation circuitry function over the migraine cycle - Marciszewski, K.K.; Meylakh, N.; Harrington, Flavia; Mills, E.P.; Macefield, V.G.; Macey, P.M.; Henderson, L.A. (SOC NEUROSCIENCE, 2018)
© 2018 the authors. The neural mechanism responsible for migraine remains unclear. While an external trigger has been proposed to initiate a migraine, it has also been proposed that changes in brainstem function are critical for migraine headache initiation and maintenance. Although the idea of altered brainstem function has some indirect support, no study has directly measured brainstem pain modulation circuitry function in migraineurs particularly immediately before a migraine. In male and female humans, we performed fMRI in 31 controls and 31 migraineurs at various times in their migraine cycle. We measured brainstem function during noxious orofacial stimulation and assessed resting-state functional connectivity. First, we found that, in individual migraineurs, pain sensitivity increased over the interictal period but then dramatically decreased immediately before a migraine. Second, despite overall similar pain intensity ratings between groups, in the period immediately before a migraine, compared with controls and other migraine phases, migraineurs displayed greater activation in the spinal trigeminal nucleus during noxious orofacial stimulation and reduced functional connectivity of this region with the rostral ventromedial medulla. Additionally, during the interictal phase, migraineurs displayed reduced activation of the midbrain periaqueductal gray matter and enhanced periaqueductal gray connectivity with the rostral ventromedial medulla. These data support the hypothesis that brainstem sensitivity fluctuates throughout the migraine cycle. However, in contrast to the prevailing hypothesis, our data suggest that, immediately before a migraine attack, endogenous analgesic mechanisms are enhanced and incoming noxious inputs are less likely to reach higher brain centers. Significance Statement It has been hypothesized that alterations in brainstem function are critical for the generation of migraine. In particular, modulation of orofacial pain pathways by brainstem circuits alters the propensity of external triggers or ongoing spontaneous activity to evoke a migraine attack.Wesought to obtain empirical evidence to support this theory. Contrary to our hypothesis, we found that pain sensitivity decreased immediately before a migraine, and this was coupled with increased sensitivity of the spinal trigeminal nucleus to noxious stimuli.Wealso found that resting connectivity within endogenous pain modulation circuitry alters across the migraine cycle. These changes may reflect enhanced and diminished neural tone states proposed to be critical for the generation of a migraine and underlie cyclic fluctuations in migraine brainstem sensitivity.